Frequency Reuse Optimization For OFDMA Network - Indra, Win Adiyansyah; Hamid, Mohd Saad; Mohd Yusof, Norfadzlia; Jayraman, Nishanthinidevi; Rusnandi, Herdy (Medwell Journals, 2019)
This study investigated the frequency reuse optimization scheme for Orthogonal Frequency Division Multiple Access (OFDMA). Forsk Atoll, Earth Explorer and Global Mapper 15 were used to deploy the simulations, local area (Ayer Keroh, 2.2667°N 102.2833°E) was selected to perform the simulation. The simulation result showed that by implementing Fractional Frequency Reuse (FFR) in Orthogonal Frequency Division Multiple Access (OFDMA) network on the area, gave a significant improvement, in term of co-channel interference and Received Signal Strength Indicator (RSSI). Very low co-channel interference and a strong signal strength occurred on the selected area by modifying the related parameters such as frequency allocation for every single sectoral antenna, antenna height, power of base station and antenna tilt degree. Limited frequency allocation available in the simulation software cause the co-channel interference still exist, although, the values are considered very unsignificant. Improvement can be made by adding frequency resources and physical drive test to validate the simulation measurement result.